ANALISIS SISTEM PERGARAMAN TRADISIONAL DI PANTAI UTARA KABUPATEN PROBOLINGGO - Mustofa Mustofa; Edy Turjono (STIE Mandala Jember, 2017)
Analysis of traditional systems on the north coast pergaraman Probolinggo district is based on characteristics of a region. Java's northern coastal waters represents the characteristic condition of coastal resources management is needed specifically especially traditional salt processing. Traditional pergaraman system on the northern coast of Probolinggo district became one of the major economic activities in coastal areas. This study aims to: (1) Identify the economic activity of traditional salt farmers in the northern coastal region of Probolinggo district; (2) Knowing the demographic characteristics, economy and culture of farming communities traditional salt in kawasanan northern coast Probolinggo district; (3) Knowing the relationships among stakeholder groups (stakeholders), namely salt farmers, traders or middlemen, government agencies, and community institutions in connection with the traditional salt farmers in the northern coastal region of Probolinggo district. This study uses a form of qualitative research conducted on an object and mengkondisikannya as it is. Data collection is done by collecting a variety of information or data about the economic activity of traditional salt farmers in the northern coastal region of Probolinggo district. From the research results can be concluded and advised efforts to improve the quality levels of NaCl 85% NaCl salt into 98% of the people in order to meet the needs of industry for salt for this disupali through import salt. The establishment of a financial institution or group-based joint venture business group of salt needs to be done to overcome this difficulty salt farmers in terms of capital in the activities of salt production and post-production so that the sales price can be sold at a high price.